Impact of Locus Control and The Work Environment on Employee Performance with Self-Efficiency as a Mediation in Paper Companies in East Java - Maya Ida Kesumawatie; Roy Sumaryono; Teguh Herdijanto (Ilomata International Journal of Management, 2021)
Human resources have a vital role in every organization to survive in the increasingly tough competition. The sophistication of communication technology and its methods will not be meaningful if the existing human resources are not skilled in using all existing facilities. Every existing organization needs human resources which have high performance. This study aimed to determine the effect of locus of control and work environment on employee performance with self-efficacy as a mediating variable. In this study, the dependent variable is employee performance, while the independent variable is the locus of control and work environment and self-efficacy as an intervening variable. This research was conducted at a paper company in East Java. The data collection method was carried out by using a census technique using a questionnaire so that the sample amounted to 100 respondents. The results showed that locus of control had a significant positive effect on self-efficacy but had no significant effect on employee performance. The work environment had a significant positive effect on employee self-efficacy and performance. In contrast, self-efficacy had a significant positive effect on employee performance and was an intervening variable between locus of control and employee performance. employee performance.